Rancangan Strategi Pemasaran Untuk Meningkatkan Daya Saing Swalayan Annisa di Pasar Lokal - Rahmad Akbar (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This research aims to formulate a more efficient marketing strategy for Swalayan Annisa, a minimarket that provides basic needs but faces challenges in maintaining service quality amidst increasingly fierce market competition. Using the SWOT analysis method, this research analyzes competitive dynamics to identify strengths, weaknesses, opportunities and threats faced by Swalayan Annisa. The analysis results show that the strength value of this minimarket is 1.92, weaknesses 0.99, opportunities 1.359, and threats 1.358. The overall score on the IFE Matrix was recorded at 2.92, while the EFE Matrix received a score of 2.71. Based on these results, this research suggests strategies to increase operational efficiency and diversify services as important steps in strengthening the market position of Annisa Supermarkets. The proposals given focus on increasing competitiveness and improving customer service to encourage more sustainable growth and maintain the existence of minimarkets in an increasingly competitive market.